Temporal expression profile of an accessory-gland protein that is transferred via the seminal fluid of the simultaneous hermaphrodite Lymnaea stagnalis. (26th March 2019) - Swart, Elferra M; Davison, Angus; Ellers, Jacintha; Filangieri, Riccardo R; Jackson, Daniel J; Mariën, Janine; van der Ouderaa, Isabelle B C; Roelofs, Dick; Koene, Joris M
Abstract: Male accessory-gland proteins are known to affect female physiology in multiple ways, maximizing a male's reproductive success—often at a cost to the female. Due to this inherent sexual conflict, accessory gland proteins (ACPs) are generally studied in separate-sex organisms. While ACPs have also been identified in simultaneous hermaphrodites as an important part of post-copulatory sexual selection processes, their study has lagged behind that of ACPs in organisms with separate sexes. In the great pond snail, Lymnaea stagnalis, an ACP affecting egg laying, ovipostatin, is produced in the prostate gland. Based on the published partial Ovipostatin gene sequence, we now provide the complete mRNA and gene sequences, and confirm that gene expression is prostate gland-specific. More importantly we observed a significant increase in Ovipostatin expression in sperm donors after ejaculation. Ovipostatin gene expression did not differ between donors giving their ejaculate first (primary donors) and those donating an ejaculate after having been inseminated (secondary donors). These observations support a role for ovipostatin in reproduction and highlight the importance of standardizing the time point when measuring expression levels of ACPs.